Is markerless motion tracking a feasible approach for in field kinematic analysis of weightlifting? - Holzer, D.; Hummel, C.; Paternoster, F. K.; Stöcker, F.; Thiele, F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In weightlifting, a quantitative kinematic analysis of an athlete can be useful to assess the performance during the snatch. A marker-based approach (MB) is widely used to obtain kinematic data in weightlifting [1]. Yet, it is not suitable for in field activities such as competitions. Recently developed markerless video-based systems (VB) working with deep learning-based pose estimation algorithms might be an alternative approach [2]. However, the applicability and accuracy of VB systems in assessing highly dynamic full body activities remain mostly unexplored. Hence, the aim of this study was to compare the kinematics of a snatch using a VB along with a MB approach.